Chemical chaperones reverse early suppression of regulatory circuits during unfolded protein response in B cells from common variable immunodeficiency patients. (9th January 2020) - Bhatt, D; Stan, R C; Pinhata, R; Machado, M; Maity, S; Cunningham-Rundles, C; Vogel, C; de Camargo, M M
Summary: B cells orchestrate pro-survival and pro-apoptotic inputs during unfolded protein response (UPR) to translate, fold, sort, secrete and recycle immunoglobulins. In common variable immunodeficiency (CVID) patients, activated B cells are predisposed to an overload of abnormally processed, misfolded immunoglobulins. Using highly accurate transcript measurements, we show that expression of UPR genes and immunoglobulin chains differs qualitatively and quantitatively during the first 4 h of chemically induced UPR in B cells from CVID patients and a healthy subject. We tested thapsigargin or tunicamycin as stressors and 4-phenylbutyrate, dimethyl sulfoxide and tauroursodeoxycholic acid as chemical chaperones. We found an early and robust decrease of the UPR upon endoplasmic reticulum (ER) stress in CVID patient cells compared to the healthy control consistent with the disease phenotype. The chemical chaperones increased the UPR in the CVID patient cells in response to the stressors, suggesting that misfolded immunoglobulins were stabilized. We suggest that the AMP-dependent transcription factor alpha branch of the UPR is disturbed in CVID patients, underlying the observed expression behavior. Graphical Abstract: